Landscape evolution in the St. Lawrence Mount area in Kałdus, between the Atlantic period and contemporary times: https://doi.org/10.26485/AGL/2018/107/3 - Luc, Małgorzata; Szmańda, Jacek B. (Acta Geographica Lodziensia, 2018)
At the beginning of the 21st century, south of Chełmno in Poland, interdisciplinary, archaeological and natural research was conducted on a large scale. At that time, extensive research material in the field of archeology, botany, geoecology, geomorphology, palynology and pedology was acquired. On its basis, and taking into account the relations of natural and anthropogenic components, the authors attempt in this publication to reconstruct the landscape from the beginning of human activity. The results of the study are presented on landscape profiles. They indicate the progressive evolution of the landscape from a Primeval landscape at the beginning of the Atlantic period, through a Natural (quasicultural) landscape in the Neolithic Age and an Agricultural-settlement cultural landscape in the Bronze Age and Iron Age, to a Settlement-agricultural cultural landscape in the Early Medieval Period.